Influence of minor combined addition of Cr and Pr on microstructure, mechanical properties and corrosion behaviors of an ultrahigh strength Al-Zn-Mg-Cu-Zr alloy. (January 2018) - Wang, Ming; Huang, Lanping; Chen, Kanghua; Liu, Wensheng
Highlights: Trace addition of Crand Printo the T6-tempered AlZnMgCu-0.16Zr alloy modified the second-phase morphology and formed additional nanophases. Nanoscale Cr- and Pr-containing Al3 Zr and Zr-containing PrCr2Al20 dispersoids inhibited the recrystallization and sub-grain growth. Trace combined addition of Cr and Pr reduced corrosion rate, improved mechanical properties and corrosion resistance. Abstract: This work focuses on controlling grain boundary structure in an ultra-high strength Al-8.6Zn-2.5Mg-2.2Cu-0.16Zr (wt.%) alloy by the combined addition of trace Cr (0.1 wt.%) and Pr (0.14 wt.%), and evaluating mechanical properties and localized corrosion behaviors of the alloy in the peak aged condition. The introduction of trace Cr and Pr leads to the formation of nanoscale Cr, Pr-containing Al3 Zr and Zr-containing PrCr2 Al20 dispersoids which can obviously inhibit the recrystallization and sub-grain growth of the super-high strength Al-Zn-Mg-Cu alloys, and retain the deformation-recovery microstructure dominated by low-angle grain boundaries. The nearly ellipsoidal dispersoids with a size of 10–35 nm are discretely distributed and precipitate free zones are hardly formed in low-angle grain boundaries. This new alloy composition exhibits better combined properties, higher resistance to stress corrosion, exfoliation corrosion and inter-granular corrosion with the undamaged strength, ductility and fracture toughness.